PEMBINAAN AKHLAK SISWA PASCA COVID-19 MELALUI KEGIATAN EKSTRAKURIKULER ROHIS - Faturrahmi Faturrahmi; Akhyar Hanif; David David (AT-TA'DIB: JURNAL ILMIAH PRODI PENDIDIKAN AGAMA ISLAM, 2022)
This article's main problem is moral development for post-Covid-19 students through Spiritual activities at the MTsM Sulit Air, Solok Regency. This study aims to describe how post-Covid-19 student morals form through extracurricular activities at MTsM Sulit Air, Solok Regency. This study uses the phenomenological method to describe conditions or phenomena that occur in the field-data collection techniques used through observation, interviews, and documentation. Data analysis techniques include data reduction, data presentation, and conclusion. Data validity technique with triangulation. Research informants are madrasa heads, teachers, and students. The results showed that post-Covid-19 student moral development was carried out through extracurricular activities at MTsM Sulit Air through three activities, namely tahsin, tahfizh and muhadharah. In addition to developing students' talents, this activity can also lead students to improve their reading of the Qur'an, and memorize the Al-Qur'an according to the correct tajwid and makhraj. In addition, it also fosters student discipline in carrying out activities on time, responsible for assignments given by the teacher, humility when exceeding friends' memorization and confidence when studying the Qur'an, daring to appear lecturing in public, responsible for preaching conveyed correctly based on the Al-Qur'an or Hadith that has been studied.